Implications law in ethics sustainable business in Indonesia - Quddus, Muh. Syah (Gema Wiralodra, 2024)
This research explores the legal implications arising in the context of sustainable business practices and their relationship with business ethics. The research methodology used is library research, where data is collected from various relevant literature sources related to the research topic. The research findings indicate that the law, especially business law, plays a crucial role in shaping sustainable business ethics. Legal implications in sustainable business ethics include environmental aspects, labor relations, social responsibility, and financial reporting. Additionally, there are legal challenges in sustainable business practices, with one of the main challenges being the complexity and differences in regulations across various jurisdictions. Therefore, a solution to address these challenges involves establishing a competent and experienced legal team, possibly collaborating with local legal advisors in each jurisdiction.